Multiletramento e afetividade: uma proposta para o ensino com gêneros orais na pré-escola - Loureiro, Soraya Nogueira Albert (2022)
Considering, as presented in the literature, that working with oral genres in preschool in an affective - motor context can directly contribute to the development of skills and abilities recommended by the BNCC; the misinterpretation of manifestations of failure by students regarding the literacy process; the prioritization of cognitive and writing aspects to the detriment of motor aspects and orality, respectively, thus constitute the core of the problem of this research. Thus, the objective of the present study is to present a proposal of activities for teaching with oral genres in preschool from the perspective of multiliteracies, affectivity, pedagogy of movement and other significant learning situations based on the objectives of knowledge and development established in the Base National Common Curricular (BNCC), in order to enhance the planning of teachers in the municipal network of the city of João Pessoa. The theoretical framework is composed by Bakhtin (2003) and Marchuschi (2010) to discuss the 3rd conception of language; Walon (1968), Vygotsky (1991) e Piaget (1971) regarding the relationship between cognition and affectivity; for oral genres Soares (2002), Kleiman (2008), Scheneuwly and Dolz (1997); regarding the multiliteracies Rojo and Moura (2012), Street (2013, 2014), Malta (2015); on meaningful learning Ausubel (1963); with regard to the pedagogy of the movement Freire (1997), Vilela (2015), Vieira (2017), Menezes (2006), Betti and Zulliani (2002), Sayão (1996), Ayoub (2001). The proposed activities were selected/adapted from two perspectives: report presented by Loureiro (2018) in the 11th edition of the Brazilian Teachers Award and significant learning situations published in books, websites, blogs and channels. Such activities culminated in a software called Tralalá, which in addition to presenting the detailed proposal with 20 activities, materials, learning objectives based on the BNCC and variation totaling 40 possibilities, will include elements from the perspective of multiliteracies to optimize the teacher's time and facilitate their planning. After completion and instrumentation of the tool, we envision the possibility of recording new activities carried out by teachers and/or adaptations arising from the performance of the proposed activities, in order to share knowledge and new experiences, further enriching the collection of possibilities. Within this context, in fact, we would not have a ready and finished tool, but a tool that is configured as the educational process itself, which would be constantly updated, feeding itself back through the search, realization and readjustment of the action.